Business lecturers' commitments of entrepreneurship subject in UiTM Pahang / Noor Affeeda Ramli ...[et al.] - Ramli, Noor Affeeda; Abd Wahid, Nomilia; Abd Aziz, Nurul Nadia; Ishak, Maisarah (2014)
The Ministry of Education (MOE) has emphasizes entrepreneurship element to be inculcated among the graduates. In conjunction with MOE higher education objective, UiTM took initiatives in introducing entrepreneurship subject/ENT300 to all faculties. It is a compulsory subject to the students in completing their program. In order to engage students with an entrepreneurial career, the lecturers should equip themselves with sufficient knowledge on how to teach the course. Therefore, this study was conducted to investigate the degree of commitment among faculty lecturers' who are currently teaching the course ENT300. The level of commitment in teaching has been significantly proved in literatures to have a positive impact on student's performance. A total of 33 self-administered questions are distributed to the Faculty Business Management (FBM) lecturers' in UiTM Pahang. The data was tabulated using SPSS version 20.0 for descriptive statistics. The results with the highest mean of 4.30 revealed that the respondents were fully committed to teach entrepreneurship, while mean of 4.15, revealed that teaching entrepreneurship really inspires them to give of their very best in the way of job performance. This was the most positive signs for the development of entrepreneurship education, will result in generating active entrepreneurial culture within the institution.